PENGARUH RASIO CAPITAL, ASSET, EARNING DAN LIKUIDITAS TERHADAP PROFITABILITAS (ROA) PADA PT. BANK ACEH SYARIAH, Tbk. PERIODE 2011-2020 - Annisa Suci Ramadhani; Imsar; Nurul Jannah (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2021)
This study aims to determine the effect of the ratio of capital, assets, earnings, liquidity on profitability (ROA) at PT. Aceh Sharia Bank. This study uses a quantitative approach with data sources from secondary data. This study uses a documentation study research method using data from financial balance reports, profit sharing distributions and financial ratios on a quarterly basis from 2011-2020 at PT. Bank Aceh Syariah, Tbk the analytical technique used is multiple linear regression test using SPSS 25.0 analysis tool. The results of this study indicate that partially (T test) the CAR variable has a positive and insignificant effect on Return On Assets (ROA) at PT. Bank Aceh Syariah, Tbk with a tcount of 1.224 and a significance probability value of 0.229. NPF has a positive and significant effect on Return On Assets (ROA) at PT. Bank Aceh Syariah, Tbk with a tcount of 3.255 and a significance probability value of 0.003. BOPO has a negative and significant effect on Return On Assets (ROA) at PT. Bank Aceh Syariah, Tbk with a tcount of -17,140 and a significance probability value of 0.000. And FDR has a negative and insignificant effect on Return On Assets (ROA) at PT. Bank Aceh Syariah, Tbk with a tcount of -0.407 and a significance probability value of 0.686. In this study, the more dominant variable that has an influence on the profitability of Return On Assets (ROA) is the NPF variable. And simultaneously the variables CAR, NPF, BOPO, FDR have a significant effect on Return On Assets (ROA) with a significant value of 0.000 and the Fcount value of 97.495 or greater than the Ftable value of 2.64. The value of the coefficient of determination is 91.8%.